Analyzing the Word Formation of Slang Vocabulary Employed by Fathia Izzati on YouTube - Fadhillah, Nurul; Nurweni, Ari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Slang is a form of language, expressions, or specialized language usage commonly found in informal conversations, particularly within specific groups. Fathia Izzati, known as